End of season influenza vaccine effectiveness in adults and children in the United Kingdom in 2017/18 - Pebody, R; Djennad, A; Ellis, J; Andrews, N; Marques, D; Cottrell, S; Reynolds, A; Gunson, R; Galiano, M; Hoschler, K; Lackenby, A; Robertson, C; et al. (European Centre for Disease Prevention and Control, 2019)
BackgroundIn the United Kingdom (UK), in recent influenza seasons, children are offered a quadrivalent live attenuated influenza vaccine (LAIV4), and eligible adults mainly trivalent inactivated vaccine (TIV).AimTo estimate the UK end-of-season 2017/18 adjusted vaccine effectiveness (aVE) and the seroprevalence in England of antibodies against influenza viruses cultured in eggs or tissue.MethodsThis observational study employed the test-negative case-control approach to estimate aVE in primary care. The population-based seroprevalence survey used residual age-stratified samples.ResultsInfluenza viruses A(H3N2) (particularly subgroup 3C.2a2) and B (mainly B/Yamagata/16/88-lineage, similar to the quadrivalent vaccine B-virus component but mismatched to TIV) dominated. All-age aVE was 15% (95% confidence interval (CI): -6.3 to 32) against all influenza; -16.4% (95% CI: -59.3 to 14.9) against A(H3N2); 24.7% (95% CI: 1.1 to 42.7) against B and 66.3% (95% CI: 33.4 to 82.9) against A(H1N1)pdm09. For 2-17 year olds, LAIV4 aVE was 26.9% (95% CI: -32.6 to 59.7) against all influenza; -75.5% (95% CI: -289.6 to 21) against A(H3N2); 60.8% (95% CI: 8.2 to 83.3) against B and 90.3% (95% CI: 16.4 to 98.9) against A(H1N1)pdm09. For ≥ 18 year olds, TIV aVE against influenza B was 1.9% (95% CI: -63.6 to 41.2). The 2017 seroprevalence of antibody recognising tissue-grown A(H3N2) virus was significantly lower than that recognising egg-grown virus in all groups except 15-24 year olds.ConclusionsOverall aVE was low driven by no effectiveness against A(H3N2) possibly related to vaccine virus egg-adaption and a new A(H3N2) subgroup emergence. The TIV was not effective against influenza B. LAIV4 against influenza B and A(H1N1)pdm09 was effective.